Tauhid Uluhiyah - Anhar Anhar (LP2M IAIM Sinjai, 2019)
Tawhid as a concept of faith and devotion to Allah SWT is the foundation for Islam. A Muslim knows his identity and religion through this kind of concept. Then he can observe the world, life, science, norms and values, and it becomes the main standard in judging the right and wrong of people's beliefs and beliefs. Al uluhiyah, unites or unites Allah swt from all forms of worship, both spiritual and spiritual, that there is no god worthy of worship except Allah swt and he who upholds justice. In this paper, it is analyzed thematically with some literature and understanding on the topic raised by the author.